Soluble form of carbonic anhydrase IX (CA IX) in the serum and urine of renal carcinoma patients - Závada, J (Nature Publishing Group, 2003)
Tumour-associated protein carbonic anhydrase IX (CA IX) has two major forms. One is a cell-associated, transmembrane protein seen on Western blots as a twin band of 54/58 kDa, expressed in gastric mucosa and in several types of cancer. The other is a soluble protein s-CA IX of 50/54 kDa, which is released into the culture medium or into the body fluids, most likely by proteolytic cleavage of the extracellular part from transmembrane and intracellular sequences. While TC media of CA IX-positive tumour cell lines or short-term cultures of tumour explants contain a relatively high concentration of s-CA IX (20–50 ng ml(−1)), the level of this antigen in blood serum and urine of renal clear cell carcinoma patients is about 1000 × lower. The concentration of CA IX in the blood and in urine varies within wide limits and there is no obvious correlation with tumour size. After nephrectomy, s-CA IX is cleared from the blood within a few days. Only an extremely low concentration of CA IX was detectable in the sera and in urine of control individuals.